2008
DOI: 10.1016/j.rmed.2008.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluticasone propionate/salmeterol (250/50μg) or salmeterol (50μg) on COPD exacerbations

Abstract: We conclude that fluticasone propionate/salmeterol 250/50 is more effective than salmeterol at reducing the rate of moderate to severe exacerbations over 1 year. The benefits of this reduction relative to the risk of a higher incidence of reported pneumonia should be considered. This study supports the use of fluticasone propionate/salmeterol 250/50 for the reduction of COPD exacerbations in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
174
1
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(196 citation statements)
references
References 31 publications
(29 reference statements)
12
174
1
9
Order By: Relevance
“…Although MAIT cells may not be required for defense against monomicrobial infections with S. pneumoniae, a deficiency of MAIT cells in nonstreptococcal bacterial sepsis has been described in the intensive care setting, and is associated with increased acquisition of nosocomial infections (47). Thus, our findings may begin to provide an explanation for the increased risk of pneumonia associated with ICS use in COPD (13)(14)(15)(16)(17)(18). In addition, although NTHi is a commensal of the upper respiratory tract, it is not present as a persistent, distinct microbial community in the lower respiratory tract in health.…”
Section: Cd161mentioning
confidence: 71%
See 1 more Smart Citation
“…Although MAIT cells may not be required for defense against monomicrobial infections with S. pneumoniae, a deficiency of MAIT cells in nonstreptococcal bacterial sepsis has been described in the intensive care setting, and is associated with increased acquisition of nosocomial infections (47). Thus, our findings may begin to provide an explanation for the increased risk of pneumonia associated with ICS use in COPD (13)(14)(15)(16)(17)(18). In addition, although NTHi is a commensal of the upper respiratory tract, it is not present as a persistent, distinct microbial community in the lower respiratory tract in health.…”
Section: Cd161mentioning
confidence: 71%
“…However, effects of ICS are modest and likely restricted to certain subgroups of this heterogeneous condition (3) whereas evidence is accumulating from well-designed clinical trials that ICS increase the incidence of community-acquired pneumonia (13)(14)(15)(16)(17)(18). The mechanisms underlying this effect remain unknown, and have been highlighted as a research priority (3).…”
mentioning
confidence: 99%
“…Similar to TB risk, the risk of pneumonia in COPD patients also relates to the dosage of ICS. While lower doses of fluticasone/salmeterol (500 μg/day) pose a risk of pneumonia [51], Ernst and co-workers reported that an increased RR of hospitalization for pneumonia correlated with higher ICS doses i.e., fluticasone at 1,000 μg/day or more (RR of 2.25 [95% CI: 2.07-2.44]) [52]. The risk of pneumonia development connected with inhaled corticosteroid-containing medicines used in COPD treatment has recently been confirmed by the European Medicines Agency but the agency did not find conclusive evidence of differences in risk between distinct classes of ICS drugs [53].…”
Section: Chronic Airway Disease As a Risk Factor For The Development mentioning
confidence: 99%
“…(17) In patients with moderate or severe COPD, as determined by the GOLD classification, the use of salmeterol in combination with fluticasone was shown to be superior to the use of SABAs in combination with SAMAs, (18) as well as to the use of salmeterol in isolation. (19)(20)(21) In patients with severe or very severe COPD, as determined by the GOLD classification, there were no differences between the salmeterol-fluticasone and formoterolbudesonide combinations in terms of symptom The process of selection allowed us to include 84 original articles in the present review. Many of those articles addressed more than one class of medication and various outcomes, which generated 420 analyses.…”
Section: Article Selectionmentioning
confidence: 99%
“…Donohue et al (16) found no significant differences between patients treated with formoterol and those treated with salmeterol regarding the number of exacerbations occurring in one year. In the analyses evaluated, the use of LABAs and ICs in combination was shown to be superior to that of LABAs or ICs in isolation for the following outcome measures (19)(20)(21)43,47) : number of exacerbations; severe exacerbations requiring hospitalization; and use of systemic corticosteroids.…”
Section: Exacerbationmentioning
confidence: 99%